2010
DOI: 10.1124/mol.110.069971
|View full text |Cite
|
Sign up to set email alerts
|

Further Characterization of the Electrogenicity and pH Sensitivity of the Human Organic Anion-Transporting Polypeptides OATP1B1 and OATP1B3

Abstract: Organic anion-transporting polypeptides (OATPs) are involved in the liver uptake of many endogenous and xenobiotic compounds, such as bile acids and drugs, respectively. Using Xenopus laevis oocytes and Chinese hamster ovary (CHO) cells expressing rat Oatp1a1, human OATP1B1, or OATP1B3, the sensitivity of these transporters to extracellular/intracellular pH (pHo/pHi) and changes in plasma membrane potential (⌬⌿) was investigated. In X. laevis oocytes, nonspecific plasma membrane permeability increased only at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 40 publications
1
26
1
Order By: Relevance
“…Oatp1d1 activity was affected by pH o and pH i changes, which in turn induced changes in proton fluxes across the plasma membrane (Figs. 7 (A and B) Ϫ ] antiport, which was previously proven for several mammalian OATPs/Oatps (26,45). In contrast, when [H ϩ ] gradient was reversed (pH i Ͻ pH o ) through intracellular acidification or extracellular alkalization, we observed significant reduction in Oatp1d1 transport activity (Fig.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Oatp1d1 activity was affected by pH o and pH i changes, which in turn induced changes in proton fluxes across the plasma membrane (Figs. 7 (A and B) Ϫ ] antiport, which was previously proven for several mammalian OATPs/Oatps (26,45). In contrast, when [H ϩ ] gradient was reversed (pH i Ͻ pH o ) through intracellular acidification or extracellular alkalization, we observed significant reduction in Oatp1d1 transport activity (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…The majority of OATPs/ Oatps, including OATP1A2, OATP1B1, and OATP1B3, function as [HCO 3 Ϫ ] antiporters (15,26,45,46). However, some rat transporters, namely Oatp1a1 and Oatp1a4, use glutathione for the antiport (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…two times the number of microrate constants), there are only 9 unknown variables, since k 4 is assumed to be the same value for each compound, as they were measured against the same transporter in the same expression system and k 4 is purely transporter-specific. While there has been evidence k 4 can be partially influenced by exchanged substrates in limited cases (12), it is assumed here that k 4 is substrate-independent. Compound pair analysis is of practical value, as Michaelis-Menten parameters are typically interpreted in the context of other compounds.…”
Section: Methodsmentioning
confidence: 99%
“…For example, substrate affinity can be increased by protonation of a conserved histidine residue at the extracellular side of transmembrane domain 3 (Leuthold et al, 2009). Similarly, studies using Xenopus laevis oocytes, Caco-2 cells, and Chinese hamster ovary cells showed that OATP1A2, OATP1B1, and OATP1B3 transport function is dependent upon an electrogenic gradient and that these transporters are strongly affected by fluctuations in external pH (Kato et al, 2010;Martinez-Becerra et al, 2011). However, pH dependence of OATP1B1-and OATP1B3-mediated transport remains controversial since Mahagita et al (2007) showed that estrone-3-sulfate transport via either OATP1B1 or OATP1B3 was unaffected by changes in extracellular pH.…”
Section: E Oatp5/oatp6 Familymentioning
confidence: 99%